Undoing mastery: With ambivalence?. Issue 1 (March 2021) - Linz, Jess; Secor, Anna J
In this commentary, we respond to Derek Ruez and Daniel Cockayne's article 'Feeling Otherwise: Ambivalent Affects and the Politics of Critique in Geography'. We do so by picking up ambivalence—or more precisely, ambivalence about ambivalence—as a tool with which Ruez and Cockayne leave us. We find this tool somewhat difficult to grasp, but we understand this as part of its design. Ambivalence undoes the subject's mastery. In doing so, we find that an airing of ambivalence gives other kinds of entangled, indeterminate, and unknowing relations room to breathe.